Developing Picture Series Media To Teach Reading Comprehension For 11th Grade Students Of Ma Bustanul Muta’allimin: English - Ratna Oktaverima; Istina Atul Makrifah; Tyas Alhim Mubarok (Journal of English Development, 2024)
This study aims to determine the process and results of developing a picture series to teach English reading skills for explanatory text material. The sample of this research is the XI grade students of MA Bustanul Mutaalimin which amounted to 19 people. Students learn many things at school, including learning languages.  This type of research is Research and Development (R&D) using the ADDIE model. The data in this study were collected through observation, unstructured interviews, and questionnaires. The data were analyzed using a manual percentage formula. The results were obtained from the validation of instruments, media, and materials. The percentage of media expert validation gets a value of 83% which means "very valid", and material expert validation gets a value of 72.5% which means "valid". In addition, the results of student responses about the media get a score of 81,57% which means "very satisfied". In conclusion, the picture series learning media is ready to be used by teachers as a learning media.